HQEBSKG: Hybrid Query Expansion Based on Semantic Knowledgebase and Grouping. Issue 5 (3rd September 2022) - Keyvanpour, Mohammad Reza; Zandian, Zahra Karimi; Abdolhosseini, Zahra
Abstract : Increasing size of web leads to relevant information extraction by traditional and last query expansion methods not to be efficient and encounter an essential challenge. Therefore, to improve query expansion, in this paper, a novel hybrid method called HQEBSKG is introduced. In the first part, a new and efficient technique is proposed based on semantic knowledgebase to expand users' queries. In the following part, a useful method based on semantic relations between words is also suggested for query expansion. In the current work, to achieve the semantic relations, FarsNet and WordNet ontologies are used simultaneously to enrich knowledge resources. The experimental results show performance improvement.